2011
DOI: 10.1111/j.1600-051x.2011.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between periodontitis and metabolic syndrome among a Korean nationally representative sample of adults

Abstract: MS is associated with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
100
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 39 publications
14
100
6
1
Order By: Relevance
“…[5] yes/no When you drink water, do you feel the pain in teeth and gums? [6] yes/no When getting up in the morning, is it sticky in the mouth?…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] yes/no When you drink water, do you feel the pain in teeth and gums? [6] yes/no When getting up in the morning, is it sticky in the mouth?…”
Section: Appendixmentioning
confidence: 99%
“…4 It has been discovered that CPD is associated with systemic diseases, such as MetS, [5][6][7] coronary heart disease, 8,9 and CPD is associated with endothelial dysfunction. 10 Because CPD and ED share common risk factors, the epidemiological and pathophysiological linkage between CPD and ED is quite possible.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 8% to 10% of American adults have some form of periodontitis, on the other hand, Kwon et al 6) reported that the prevalence of periodontitis is 73.4% among aging over 19 years old in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The association between systemic health conditions and oral health has been examined in many studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Individuals with systemic health condition such as obesity, diabetes, hypertension, and hypercholesterolemia were found to have higher risk of developing periodontal disease than those without systemic health conditions [5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%